Cambridge English IELTS 2 with answers : (Cambridge University press, 2017)
This collection of practice material for the International English Language Testing system (IELTS) has been specially prepared for publication by the University of Cambridge Local Examinations Syndicate. It provides students with an excellent opportunity to familiarise themselves with IELTS and to practise examination techniques using authentic test material. This book includes an introduction to these different modules together with an explanation of the scoring system used by Cambridge ESOL. The inclusion of a comprehensive section of answers and tapescripts means that the material is ideal for students working partly or entirely on their own.